Fabrication and characterization of nanocrystalline ODS-W via a dissolution-precipitation process. (April 2019) - Wang, R.; Xie, Z.M.; Wang, Y.K.; Song, J.P.; Fang, Q.F.; Liu, R.; Jiang, Y.; Yang, J.F.; Zhang, T.; Wang, X.P.; Liu, C.S.
Abstract: In this paper, high density nanocrystalline W with uniform dispersion of nanosized oxide particles was fabricated via a dissolution-precipitation process by well controlled high-energy ball milling of the raw powder materials of Y2 O3, Ti and W and the subsequent spark plasma sintering (SPS). XRD and TEM analysis revealed that the Y2 O3 and Ti were dissolved in W matrix during the high-energy ball milling and the Y2 Ti2 O7 particles were precipitated in the SPS process, resulting in the refinement in both W grains and oxide particles. The average grain size of W is 67 nm. The average size of particles in grain interior and at grain boundaries is 8.5 nm and 16.4 nm, respectively. The Vickers microhardness of such a nanostructured W alloy is as high as 1441 Hv, which is 2–3 times that of the ever reported W alloys. Such a dissolution-precipitation process offers a general pathway for manufacturing nanocrystalline refractory metals with dispersion of nanoscale oxides in a controllable manner. Highlights: A novel powder metallurgy approach to fabricate high density nanostructured tungsten based alloys. A WYT alloy contains nanosized tungsten grains ( 67 nm) and nano oxide particles ( 10 nm). An unprecedented high Vickers microhardness of 1441 Hv has been achieved. The refining mechanisms include molecular-level dissolution and precipitation.